ANALISIS NILAI-NILAI MODERASI BERAGAMA DI MADRASAH ALIYAH AL-ITTIHADIYAH MEDAN - Lubis, Reza Noprial; Safran, Safran; Siregar, Panomoran; Nurmawati, Nurmawati; Saputra, Anri (STKIP Pesisir Selatan, 2025)
The practice of implementing the value of moderation in madrasas still faces a number of challenges. Some of them are teachers' limited understanding of the concept of moderation in depth, pressure from certain conservative groups, and the negative influence of social media that often spreads intolerance narratives. This shows that strengthening the value of religious moderation in education requires a comprehensive and sustainable strategy. Based on the description above, the researcher is interested in further analyzing the Values of Religious Moderation at MA Al-Ittihadiyah Medan. This research uses a qualitative approach with a case study approach and the subjects involved are school principals, PAI teachers and students. Based on the results of data analysis, this study reveals that the values of religious moderation taught at MA Al-Ittihadiyah Medan include the principles of tolerance, peace, diversity, and respect for differences. The novelty in this research is that there are supporting factors in strengthening the values of religious moderation at MA Al-Ittihadiyah Medan, including the commitment of madrasah leaders, such as the Head of Madrasah, who actively conveys messages of nationality and diversity on various occasions.